(untitled) (CIPEEX, 2025)
The MobSocial platform was developed to connect volunteers with organizations in need of support for social projects. Its primary objective is to facilitate interaction between these groups through an intuitive and accessible digital platform. Volunteers can register, edit their profiles, search for projects, and sign up to participate. NGOs can create, manage, and promote projects, as well as publish newsletters to keep volunteers informed about their activities. The MobSocial architecture leverages modern technologies, including Docker for virtualization, PostgreSQL for the database, React.js for the front-end, and Nest.js for the back-end, ensuring a secure, efficient, and maintainable system. Accessibility and security best practices are incorporated, along with automated testing to guarantee functionality. Future enhancements include implementing Artificial Intelligence to improve user support. This project serves as a case study in scalable system development, focusing on user experience and efficient social project management to foster greater engagement between volunteers and NGOs.